Penegakan Hukum Pidana dalam Tindak Pidana Perjudian di Kabupaten Sukoharjo - Anjas Hajju Nasrulloh (Jurnal Hukum Lex Generalis, 2026)
This study aims to analyze criminal law enforcement against gambling practices in Sukoharjo Regency in accordance with the National Criminal Code. Gambling is a crime that is prevalent in society, both conventionally and digitally. The research was conducted empirically using a legislative and sociological approach. It utilized literature studies, laws and data on gambling handling at the Sukoharjo Police Department. The study's findings indicate that criminal law enforcement against gambling in Sukoharjo Regency is implemented through repressive and preventive measures, despite facing various obstacles such as low public legal awareness and inadequate oversight of technology-based gambling practices. This requires intensive enforcement operations, inter-agency coordination and community participation.